Product Strategy and Distribution of Educational Services - Sobihah, Hani; Holid, Agus; Zohriah, Anis; Djabidi, Faizal (Advances In Social Humanities Research, 2025)
Marketing educational services is a crucial aspect in creating value for education providers and prospective students. The right product and distribution strategy can influence the competitiveness of educational institutions in an increasingly competitive market. This article examines the four main components in the educational services marketing mix, namely the elements of the marketing mix, the educational services product mix, the creation of educational service products, and the distribution of educational services. With this approach, universities can design marketing strategies that are effective, relevant and responsive to market needs. This article also discusses the challenges faced by educational service providers in implementing effective marketing strategiesproduct strategy